ESS 가치평가 기반 PV-ESS 연계 EV 충전스테이션 사업 타당성 분석 - 이지현(Ji Hyun Lee); 제갈성(Seong Jegar); 정용찬(Yong Chan Jung); 윤아윤(Ah-Yun Yoon) (Current Photovoltaic Research, 2023)
In order to deploy the large-scale energy storage (ES) service in the various industry, it is very important to develop a business model with high technological and economic feasibility through detailed valuation of cost and expected benefits. In relation to this, this paper established an optimal scheduling plan for electric vehicle charging stations connected with photovoltaic (PV) and ES technologies in Korea using the distributed energy resource valuation tool and analyzed the feasibility of the project. In addition, the impact of incentives such as REC (Renewable Energy Certificate) to be given to electric vehicle charging stations in accordance with the relevant laws to be revised in the future was analyzed. As a results, the methodology presented in this paper are expected to be used in various ways to analyze the feasibility of various business models linked to renewable energy and ES technologies as well as the electric vehicle market.